Técnicas de soldadura en estructuras metálicas y su incidencia en la enseñanza-aprendizaje en la asignatura de mecánica general de los estudiantes del bachillerato de la unidad educativa San Rafael del cantón Yaguachi, provincia del Guayas - Chang Peñaherrera, Javier Alejandro (2017)
The present final report of the research project corresponds to a study carried out to the students of the baccalaureate in the subject of general mechanics of the unit educational program “San Rafael”, an investigation into the problems faced by the students of said institution, in this way this work is developed with in the educational institution to work in a real field the theme of the project. The obtaining of data for this project was the survey in its interview modalities that was made to both teachers and students in the area in question and who would be beneficiaries, with the application of this educational project, the questionnaire as an instrument to obtain the information. In addition, the obtaining data through the qualitative and quantitative methodology, in addition to analyze the information determining the shortcomings and opportunities, who would present this proposal. It was concluded that the workshop of the general mechanics area of the educational institution where this project has many shortcomings with regard to machines, tools and support materials, for students to do their practices, and of this they are aware the campus authorities. To finalize this summary, a proposal was presented on the parameters of pedagogical guides on the different types of welding techniques that improve student learning on the subject.